The tumor microenvironment shapes lineage, transcriptional, and functional diversity of infiltrating myeloid cells - Elpek, Kutlu G. (2014)
Myeloid cells play important regulatory roles within the tumor environment by directly promoting tumor progression and modulating the function of tumor-infiltrating lymphocytes, and as such, they represent a potential therapeutic target for the treatment of cancer. Although distinct subsets of tumor-associated myeloid cells have been identified, a broader analysis of the complete myeloid cell landscape within individual tumors and also across different tumor types has been lacking. By establishing the developmental and transcriptomic signatures of infiltrating myeloid cells from multiple primary tumors we found that tumor-associated macrophages (TAMs) and tumor-associated neutrophils (TANs), while present within all tumors analyzed, exhibited strikingly different frequencies, gene expression profiles, and functions across cancer types. We also evaluated the impact of anatomic location and circulating factors on the myeloid cell composition of tumors. The makeup of the myeloid compartment was determined by the tumor microenvironment rather than the anatomic location of tumor development or tumor-derived circulating factors. Pro-tumorigenic and hypoxia-associated genes were enriched in TAMs and TANs compared with splenic myeloid-derived suppressor cells. While all TANs had an altered expression pattern of secretory effector molecules, in each tumor type they exhibited a unique cytokine, chemokine and associated receptor expression profile. One such molecule, haptoglobin, was uniquely expressed by 4T1 TANs and identified as a possible diagnostic biomarker for tumors characterized by the accumulation of myeloid cells. Thus, we have identified considerable cancer-specific diversity in the lineage, gene expression, and function of tumor-infiltrating myeloid cells.